"The metaphysical objection" and concurrentist co-operation - Miller, Timothy David (Religious studies, 2022)
The foundation of W. Matthews Grant's project in Free Will and God's Universal Causality is his Non-Occasionalist version of Divine Universal Causality (NODUC), which affirms the traditional concurrentist idea that God and secondary causes cooperate non-superfluously in such a way that they both produce the entire effect. Grant defends NODUC's concurrentist account by responding to ‘The Metaphysical Objection’, which alleges that concurrentism places an inconsistent set of demands upon secondary causes. I argue that Grant's responses to that objection are unconvincing, and thus, he fails to demonstrate that NODUC is a stable foundation for the rest of his project.